Improved NH3-SCR deNOx activity and tolerance to H2O & SO2 at low temperature over the NbmCu0.1-mCe0.9Ox catalysts: Role of acidity by niobium doping. (1st November 2021) - Zhang, Zhiping; Li, Yingying; Yang, Piaoping; Li, Yushi; Zhao, Chen; Li, Rumin; Zhu, Yujun
Graphical abstract: Highlights: Nb0.06 Cu0.04 Ce0.9 Ox catalyst obtained excellent NH3 -SCR activity at 150–390 °C. Improving SO2 and H2 O resistance over Nb0.06 Cu0.04 Ce0.9 Ox catalyst by introducing Nb. Stronger surface acidity plays a key role in improving activity at low temperature. Tuning the synergistic effect between redox and acidity by Nb addition. Abstract: A series of Nbm Cu0.1-m Ce0.9 Ox catalysts were synthesized with the help of citric acid method, and used for the selective catalytic reduction of NOx with NH3 (NH3 -SCR). The catalytic performance of the Nbm Cu0.1-m Ce0.9 Ox samples was greatly improved after the introducing of niobium. Among all catalysts, the Nb0.06 Cu0.04 Ce0.9 Ox catalyst revealed the best low-temperature SCR activity, higher N2 selectivity and extraordinary SO2 and H2 O durability with 100% NO conversion at 150–390 °C. The various characterization techniques were carried out to investigate the effect of niobium doping on the physical structures, surface properties and NH3 -SCR activity of catalysts. Results reveal that the oxidation ability decrease but the acidity is enhanced with the Nb addition. The improved acidity by niobium doping is considered the primary cause for the superior deNOx performance of the Nb0.06 Cu0.04 Ce0.9 Ox catalyst at low temperature, which can offset the negative effects of the reduced oxidation ability on activity. Furthermore, in situ DRIFTS results were applied for the investigation of the reaction process in detail.